Comparative evaluation of a novel environmentally responsive modular wall system based on integrated quantitative and qualitative criteria. (1st December 2019) - Kyriakidis, A.; Michael, A.; Illampas, R.; Charmpis, D.C.; Ioannou, I.
Abstract: The present study examines the overall assessment of a novel environmentally responsive modular masonry wall system (EcoBrick). The system consists of modular construction components that are produced using an eco-friendly mix design, in which 50% w/w of the binder and aggregate are replaced by waste materials and industrial by-products. Steady-state and transient heat numerical analyses are carried out to determine the system's thermal performance, i.e. U-value, time lag and decrement factor, while data from the literature are used to assess its environmental impact in terms of embodied energy and carbon. The results are compared against corresponding data referring to common contemporary construction systems. The overall efficiency of the proposed building solution is further evaluated via a comparative qualitative analysis of various aspects associated with construction practices, in-service use and aesthetic quality. The outcomes obtained indicate that the novel masonry system EcoBrick hereby examined has excellent prospects and can be effectively adopted by the building industry, provided that a higher technological matureness level is attained. Highlights: Integrated design of a novel modular wall system offers a sustainable alternative. Comparative evaluation of different types of commonly used walling systems. Steady-state and transient heat numerical analyses show high thermal performance. Quantitative analyses show low environmental impact as to embodied energy and carbon. Qualitative analyses indicate construction efficiency compared to current practices.